Factors Related to Personal Financial Planning of Officers of Banque Pour Le Commerce Exterieur Du Laos Luangprabang Branch - XAYYAVONG, Somphong; YANGSANSAY , Chahue; VATTHANA, Mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
In this study, studying the factors affecting the personal financial planning of the employees of the Foreign Commercial Bank of Laos, Mass., Luang Prabang branch, the purpose of the study is to study the behavior in the personal financial planning of the employees of the Commercial Bank of Laos, Mass., Luang Prabang branch, to study the factors that influence the personal financial planning of the employees of the Commercial Bank, Laos, Mass., Luang Prabang, and to study the relationship between personal factors to the personal financial planning of the employees of the Commercial Bank, Laos, Mass., Luang Prabang branch by quantitative analysis using questionnaires and bringing the results to the data analysis and statistical analysis. The results of the study found that: the behavior in personal financial planning of employees of the Lao People's Foreign Commercial Bank, Luang Prabang branch, with the majority of them planning on their own, 73 people accounting for 74.5%, most of them depositing money with banks or financial institutions, with the number of 56 people accounting for 57.1%, the main purpose of financial planning, with the majority of people planning for financial freedom, with the number of 31 people accounting for 31.6%, and financial planning by investing, with the majority of people investing in business (buying property, buildings, factories, accounting for 50.40% of people). Planning to buy or own property. The type of plan to buy or own, mostly real estate such as houses, land. The value is 56 people, covering 44.4%. Planning in terms of debt. The type of debt, mostly housing credit, there are 38 people, covering 28.6%. Factors that influence personal financial planning found that both internal and external factors that influence personal financial planning of Lao Foreign Trade Bank employees, Luang Prabang branch, as a whole have a static value that has a great effect on employees.